Review of "Science and Other Cultures: Issues in Philosophies of Science and Technology" - James, Christine (Essays in Philosophy A Biannual Journal, 2004)
Dialogue between feminist and mainstream philosophy of science has been limited in recent years,although feminist and mainstream traditions each have engaged in rich debates about key concepts and their efficacy. Noteworthy criticisms of concepts like objectivity, consensus, justification, and discoverycan be found in the work of philosophers of science including Philip Kitcher, Helen Longino, Peter Galison, Alison Wylie, Lorraine Daston, and Sandra Harding. As a graduate student in philosophy of science who worked in both literatures, I was often left with the feeling that I had joined a broken familywith two warring factions. This is apparent in the number of anthologies that have emerged on both sidesin the aftermath of the “Science Wars” (Gross, Paul R., Norman Levitt, and Martin W. Lewis, eds. 1996;Koertge, Noretta, ed. 1998; Sokal, Alan and Jean Bricmont. 1998; etc.)
James, Christine (2004). Review of "Science and Other Cultures: Issues in Philosophies of Science and Technology". Essays in Philosophy A Biannual Journal. 1 electronic record (PDF).
Keywords: Philosophy, Philosophy of Science, Feminist Theory, History of Science